The changing determinants of high school attainment in rural China - Juan Yang; Terry Sicular; Desheng Lai (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2013)
The substantial shift in rural schooling levels and the contemporaneous changes in educational finance policy including tax and fees reform, two exempt and one compensation policy and school rearrangement policy, raise the need for a fresh look at the determinants of rural education. In this paper we have examined the determinants of rural high school attainment and changes in those determinants between the years 2002 and 2007 at multiple levels (individual, family and community level). We find that the increasing importance of community versus household and individual factors in determining rural children's schooling attainment between 2002 and 2007. In addition, government expenditures have a significant and positive impact on high school attainment in both years, with a shift in the relative importance of budgetary versus extrabudgetary funding.
Keywords: 330; rural education; high school attainment; family background; public finance; human capital; China